ECOLOGY AND PRODUCTION IN TWO SANDY BEACHES OF GOA (PART A) DISTRIBUTION OF BACTERIA IN COLVA AND SIRIDAON IN RELATION TO CERTAIN ENVIRON MENTAL PARAMETERS - GORE, P S; SINGBAL, S Y.S (Fishery Technology, 2016)
Qualitative . and quantitative studies on the bacterial flora of two beaches viz , Colva and Siridaon at high tide, mid-tide and low tide levels during the pre-monsoon period were made. Estimations of important nutrients, like inorganic phosphates and nitrates and organic carbon have been made and correlation with the bacterial counts is being attempted. Definite correlation between bacterial population and organic carbon is seen; however, no correlation is observed b;;tween bacterial counts and other physicochemical parameters.